Religion, society and gendered-politics in central Asia: a comparative analysis - Moniruzzaman, Md.; Kazi, Fahmida Farzana (Internaitonal Islamic University Malaysia, 2019)
Women political participation is understood to be a part of civic rights but their participation is hindered by various factors. Numerous researchers have claimed that Islam as a religion, Muslim social culture and tradition inhibit women from political participation in Muslim societies. However, there are a number of Muslim majority countries where women occupy the highest public offices and head ministries. How can this contradiction be explained. This article examines women political participation in Central Asian Muslim republics by looking at socioeconomic, parliamentary representation and informal participation factors. The study argues that socioeconomic factors in the republics still do not allow much liberal public space for women to take part in politics; however, in terms of parliamentary representation the republics maintains a record that sometimes are better off than many mature democracies. In terms of informal participation the region records better visibility of women in politics.